Countermeasures against COVID-19: how to navigate medical practice through a nascent, evolving evidence base — a European multicentre mixed methods study - Eibensteiner, Fabian; Ritschl, Valentin; Stamm, Tanja Alexandra; Cetin, Asil; Schmitt, Claus P.; Ariceta, Gema; Bakkaloğlu, Sevcan A.; Jankauskienė, Augustina; Klaus, Günter; Paglialonga, Fabio; Edefonti, Alberto; Ranchin, Bruno; et al. (BMJ open, 2021)
Objectives In a previously published Delphi exercise the European Pediatric Dialysis Working Group (EPDWG) reported widely variable counteractive responses to COVID-19 during the first week of statutory public curfews in 12 European countries with case loads of 4-680 infected patients per million. To better understand these wide variations, we assessed different factors affecting countermeasure implementation rates and applied the capability, opportunity, motivation model of behaviour to describe their determinants. - Design We undertook this international mixed methods study of increased depth and breadth to obtain more complete data and to better understand the resulting complex evidence. - Setting This study was conducted in 14 paediatric nephrology centres across 12 European countries during the COVID-19 pandemic. - Participants The 14 participants were paediatric nephrologists and EPDWG members from 12 European centres. - Main outcome measures 52 countermeasures clustered into eight response domains (access control, patient testing, personnel testing, personal protective equipment policy, patient cohorting, personnel cohorting, suspension of routine care, remote work) were categorised by implementation status, drivers (expert opinion, hospital regulations) and resource dependency. Governmental strictness and media attitude were independently assessed for each country and correlated with relevant countermeasure implementation factors. - Results Implementation rates varied widely among response domains (median 49.5%, range 20%-71%) and centres (median 46%, range 31%-62%). Case loads were insufficient to explain response rate variability. Increasing case loads resulted in shifts from expert opinion-based to hospital regulation-based decisions to implement additional countermeasures despite increased resource dependency. Higher governmental strictness and positive media attitude towards countermeasure implementation were associated with higher implementation rates. - Conclusions COVID-19 countermeasure implementation by paediatric tertiary care centres did not reflect case loads but rather reflected heterogeneity of local rules and of perceived resources. These data highlight the need of ongoing reassessment of current practices, facilitating rapid change in ‘institutional behavior’ in response to emerging evidence of countermeasure efficacy.
Gesehen am 16.12.2021